Microalgae biorefinery: An integrated route for the sustainable production of high-value-added products. (December 2022) - Okeke, Emmanuel Sunday; Ejeromedoghene, Onome; Okoye, Charles Obinwanne; Ezeorba, Timothy Prince Chidike; Nyaruaba, Raphael; Ikechukwu, Chukwudozie Kingsley; Oladipo, Abiodun; Orege, Joshua Iseoluwa
Graphical abstract: Highlights: Microalgae biorefinery for the production of biofuels, chemicals and bio-products. Impact of microalgae biorefinery on bioenergy and environmental sustainability. The potential of optimizing microalgae biorefinery for circular bio-economy. The current underlying challenges of microalgal biorefinery and future prospects. Abstract: Microalgae are pervasive organisms regarded as conservative alternatives for the sustainable synthesis of various high-value-added bio-products to replace depleting fossil fuels and reduce CO2 emissions. However, microalgae biorefinery is still very far from being commercially viable due to high costs, intensive energy requirements, and low availability of biomass and biomolecules. In this review, the current status of microalgae biorefinery is discussed by establishing the efficiency of green biotechnology in producing microalgae from wastewater and the diverse bio-products derived from the biotechnology of microalgae biorefinery. In addition, various aspects involved in the sustainable production of bulk chemicals and value-added bio-products from microalgae biorefinery, including their roles in environmental protection and the promotion of an integrated green circular bio-economy are elucidated. Lastly, the challenges facing microalgae biorefinery and recommendations to guide future research toward cost-effective, more efficient, and sustainable microalgae biorefinery are presented.